Validation of a 6-Dye Short Tandem Repeat System: A Dry Kit With Lyophilized Amplification Reagent - Li, Shuanglin; Lin, Jinfeng; Hao, Honglei; Jin, Haiying; Song, Danlu; Zhu, Bofeng (Frontiers in Genetics, 2021)
The SureID®S6 system used a lyophilized pellet as the amplification reagent to enable multiplexing of sex-determining marker Amelogenin, 21 autosomal short tandem repeats (STRs), and one Y-STR. To assess the performance, reliability, and limitation of the dry amplification system, the validation studies including PCR condition, reproducibility, sizing and precision, analytical threshold calculation, sensitivity and stochastic threshold calculation, species specificity, stability, mixture, case sample, and population and concordance were conducted according to the Scientific Working Group on DNA Analysis Methods (SWGDAM) Validation Guidelines. Experimental data suggested that the optimal range of total input DNA was from 125 to 500 pg; the appropriate analytical threshold was 80 relative fluorescence units (RFUs) while the stochastic threshold was 260 RFUs; for the stability studies, SureID®S6 system could resist against less than 500 μmol/L of hematin, 100 ng/μl of humic acid, 4 mM of indigotin, 800 mM of tannic acid, and 800 mM of calcium ion. Population and concordance studies using 500 unrelated individuals showed that the combined probability of discrimination (CPD) and cumulative probability of exclusion (CPE) values were 0.999999999999 and 0.999999998416, respectively. The genotypes for the same sample were concordant with the previously validated HUAXIA™ Platinum kit. The validation results demonstrated that the SureID®S6 system could be used for forensic applifications.